Viable system architecture applied to maintenance 4.0 - Câmara, Rafael Albuquerque (2020)
Câmara, R. A., Mamede, H. S., & Dos Santos, V. D. (2019). Viable system architecture applied to maintenance 4.0. In A. P. Abraham, J. Roth, & L. Rodrigues (Eds.), Multi Conference on Computer Science and Information Systems, MCCSIS 2019 - Proceedings of the International Conferences on Big Data Analytics, Data Mining and Computational Intelligence 2019 and Theory and Practice in Modern Computing 2019 (pp. 127-134). (Multi Conference on Computer Science and Information Systems, MCCSIS 2019 - Proceedings of the International Conferences on Big Data Analytics, Data Mining and Computational Intelligence 2019 and Theory and Practice in Modern Computing 2019). IADIS Press.